, DMCN 43: 234–8 (Developmental Medicine and Child Neurology, 2001)
AIM: To identify shared and disorder-specific molecular alterations across encephalitis, Aicardi-Goutières syndrome (AGS), and autism spectrum disorder (ASD) using cerebrospinal fluid (CSF) proteomics. METHOD: In this cross-sectional case-control study, mass-spectrometry-based proteomics was performed on archived CSF samples collected between 2016 and 2019 from children with encephalitis (n = 15, nine males, mean age 8 years 2 months, SD 3 years 8 months, range 2-13 years), genetically confirmed AGS (n = 7, five males, mean age 5 years 4 months, SD 4 years 5 months, range 1 year 10 months-14 years), and ASD (n = 10, 10 males, mean age 7 years 2 months, SD 4 years 4 months, range 2-15 years). Each cohort was compared with age-matched and sex-matched non-inflammatory neurological disorder controls. Differentially abundant proteins (false discovery rate [FDR] < 0.05) and enriched pathways were identified using Reactome. Selected proteins were validated using targeted mass spectrometry (selected reaction monitoring or high-resolution multiple reaction monitoring). RESULTS: Encephalitis showed increased immunoglobulin and acute-phase proteins, with reduced glycolysis, synaptic, and extracellular matrix proteins. AGS demonstrated increased interferon signalling, Toll-like receptor pathways, and synaptic proteins, with reduced neural structural and extracellular matrix proteins. ASD exhibited increased extracellular matrix organization and oxidative protection proteins, with decreased haemostatic and stress response proteins. Complement and innate immune pathways were enriched across all cohorts, with increased abundance of C1S, C1R, CFH, and C4A. INTERPRETATION: This hypothesis-generating study shows shared complement activation across encephalitis, AGS, and ASD, which suggests complement dysregulation as a common neuroimmune mechanism and potential biomarker in childhood neuroinflammation.